Antimony-based composite material and preparation method and application thereof
Graphene quantum doped antimony phosphate is prepared by microemulsion method and hydrothermal reaction, forming a three-dimensional sheet-like structure, which solves the problem of insufficient electrochemical performance of existing antimony phosphate materials in sodium batteries and achieves higher cyclic stability and electrical conductivity.
Patent Information
- Application Number
- CN202411990012.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing antimony phosphate materials lack electrochemical performance in sodium batteries, especially the problem of poor cycling stability under high current density.
Graphene quantum doped antimony phosphate was prepared by a microemulsion method combined with hydrothermal reaction, forming a three-dimensional sheet-like structure, and providing a phosphorus source and conductive network through 1-aminepropyl-3-methylimidazole phosphate.
The electrochemical properties of antimony-based composite materials are improved, the cycle stability and conductivity in sodium ion batteries are enhanced, and the degree of volume expansion is reduced.
Smart Images

Figure CN119390060B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrode materials, in particular to an antimony-based composite material and a preparation method and application thereof. Background Art
[0002] In recent years, electric vehicles have developed rapidly, and new energy power batteries have become an important factor restricting the development of the electric vehicle industry. The negative electrode materials in new energy power batteries have an important impact on their energy density and service life. Therefore, it is imperative to develop negative electrode materials with high capacity, good safety, long life and rich raw material sources.
[0003] As an inorganic phosphate, antimony phosphate is considered to be a potential negative electrode material for new energy power batteries. At present, antimony phosphates with different morphologies such as nanoparticles, nanorods, needles, and hollow spheres have been successfully prepared, but most of them are used as negative electrode materials for lithium batteries, and rarely used as negative electrode materials for sodium batteries. Chinese patent CN108899499A discloses a negative electrode material based on Sb / Sn phosphate, its preparation method, and its application in sodium ion batteries. The prepared SbPO4 / rGO material is a SbPO4 nanorod uniformly grown on a graphene nanosheet. When used as a negative electrode material for sodium batteries, at a current density of 1A / g, the capacity is only about 100mAh / g after 1000 cycles. How to improve the electrochemical performance of antimony phosphate as a negative electrode material for sodium batteries has become a research hotspot for researchers. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes an antimony-based composite material and a preparation method and application thereof.
[0005] The technical solutions adopted are as follows:
[0006] A method for preparing an antimony-based composite material:
[0007] Dispersing graphene quantum dots in deionized water to obtain aqueous phase A;
[0008] Add antimony trichloride into deionized water and mix well to obtain aqueous phase B;
[0009] A surfactant, n-butanol, an organic solvent and 1-aminopropyl-3-methylimidazole phosphate are mixed to obtain an oil phase, the oil phase is divided into two parts, namely oil phase A and oil phase B, and water phase A and water phase B are added to oil phase A and oil phase B respectively and stirred to obtain microemulsion A and microemulsion B;
[0010] After mixing microemulsion A and microemulsion B, quickly stir to obtain a mixed reaction liquid, transfer the mixed reaction liquid to a hydrothermal reactor, seal and heat to 100-120°C for 1-10 hours, return to room temperature after the reaction, centrifuge, collect the product, wash and dry;
[0011] The preparation method of the 1-aminopropyl-3-methylimidazole phosphate is as follows:
[0012] 1-aminopropyl-3-methylimidazolium bromide is added to deionized water, and the resulting solution is passed through an anion exchange resin to obtain an ionic liquid hydroxide solution. Phosphoric acid is added to the ionic liquid hydroxide solution, and after stirring at room temperature for 24 hours, dichloromethane is added for extraction, and the dichloromethane phase is separated, concentrated under reduced pressure, and then dried in vacuo.
[0013] Furthermore, the preparation method of the graphene quantum dots is as follows:
[0014] Add graphene oxide to nitric acid and form a dispersion by ultrasonic oscillation. Heat the dispersion to 60-80°C and react for 12-48 hours. After cooling to room temperature, adjust the pH of the solution to 7-8. Then dialyze with a dialysis bag for 1-5 days. Transfer the dialysate to a hydrothermal reactor and perform a hydrothermal reaction at 100-120°C for 5-10 hours. After cooling to room temperature, add concentrated sulfuric acid and continue the hydrothermal reaction at 120-150°C for 5-10 hours. After cooling to room temperature, adjust the pH of the solution to 7-8. Use a dialysis bag to dialyze the reaction solution again for 1-5 days. Centrifuge the dialysate and freeze-dry it at low temperature.
[0015] Furthermore, the molecular weight cut-off of the dialysis bag is 1500-3500Da.
[0016] Furthermore, the surfactant consists of Triton X-100 and CTAB.
[0017] Furthermore, the mass ratio of Triton X-100 to CTAB is 1-4:1-4.
[0018] Furthermore, the organic solvent is any one of n-pentane, n-hexane, n-heptane, and n-octane, or a combination of two or more thereof.
[0019] The present invention also provides an antimony-based composite material, wherein the antimony-based composite material is graphene quantum dots doped with antimony phosphate, and the graphene quantum dots doped with antimony phosphate has a three-dimensional lamellar structure.
[0020] The present invention also provides application of the antimony-based composite material in negative electrode materials of sodium ion batteries.
[0021] Beneficial effects of the present invention:
[0022] The invention provides an antimony-based composite material. Graphene quantum dots have abundant edge positions and good electrical conductivity, and have great potential in improving the electrochemical performance of the antimony-based composite material. The invention prepares graphene quantum dot-doped antimony phosphate by combining a microemulsion method with a hydrothermal reaction. The antimony phosphate has a three-dimensional lamellar structure, has high electrical conductivity, and has a small volume expansion degree with the change of the degree of sodium ion embedding, thereby having high cycle stability. When preparing the graphene quantum dots, carboxyl groups are modified by sulfuric acid acidification, so that the graphene quantum dots are connected to 1-aminopropyl-3-methylimidazole phosphate through hydrogen bonds or amide bonds. When antimony phosphate is generated, the 1-aminopropyl-3-methylimidazole phosphate provides a phosphorus source, and the graphene quantum dots can be uniformly dispersed in the generated antimony phosphate to form a conductive network, thereby achieving the improvement of the electrochemical performance of the antimony-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM photograph of the antimony-based composite material prepared in Example 1. DETAILED DESCRIPTION
[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0025] Embodiment 1:
[0026] This embodiment provides an antimony-based composite material which is graphene quantum dots doped with antimony phosphate and has a three-dimensional lamellar structure. Figure 1 .
[0027] The preparation method of the antimony-based composite material is as follows:
[0028] 5 g of graphene oxide was added to 400 ml of 4 mol / L nitric acid, and ultrasonically vibrated for 30 min to form a dispersion. The dispersion was heated to 70 ° C for 24 h, then cooled to room temperature, and the pH of the solution was adjusted to 8 with anhydrous sodium carbonate. Then, the solution was dialyzed with a 3500 Da dialysis bag for 5 days. The solution in the dialysis bag was transferred to a hydrothermal reactor, sealed at 120 ° C for 8 h, cooled to room temperature, and then 40 ml of concentrated sulfuric acid was added. The hydrothermal reaction was continued at 140 ° C for 8 h, cooled to room temperature, and the pH of the solution was adjusted to 8 with anhydrous sodium carbonate. The reaction solution was dialyzed again with a 3500 Da dialysis bag for 5 days, the dialyzate was centrifuged at a speed of 800 r / min to remove large pieces of precipitation, and then freeze-dried at low temperature to obtain graphene quantum dots.
[0029] 0.1 mol of 1-aminopropyl-3-methylimidazolium bromide was added to 200 ml of deionized water, and then 0.1 mol of potassium phosphate was added, and the mixture was reacted at 60°C for 10 hours. After returning to room temperature, 200 ml of dichloromethane was added for extraction, and the phases were separated. The dichloromethane phase was collected and concentrated under reduced pressure to obtain 1-aminopropyl-3-methylimidazolium phosphate;
[0030] 0.1 g of graphene quantum dots were dispersed in 10 ml of deionized water to obtain aqueous phase A;
[0031] Add 2.28 g of antimony trichloride to 10 ml of deionized water and mix well to obtain aqueous phase B;
[0032] 2.5 g of Triton X-100, 2.5 g of CTAB, 10 ml of n-butanol, 100 ml of n-hexane and 2.5 g of 1-aminopropyl-3-methylimidazole phosphate were mixed to obtain an oil phase, and the oil phase was evenly divided into two parts, denoted as oil phase A and oil phase B, and water phase A and water phase B were added to oil phase A and oil phase B respectively and stirred to obtain microemulsion A and microemulsion B;
[0033] After microemulsion A and microemulsion B are mixed, they are rapidly stirred at a speed of 500 r / min for 10 minutes to obtain a mixed reaction liquid. The mixed reaction liquid is transferred to a hydrothermal reactor, sealed and heated to 100°C for reaction for 10 hours. After the reaction is completed, the room temperature is restored and centrifuged. The product is collected, repeatedly washed with deionized water and anhydrous ethanol, and then vacuum dried at 60°C for 24 hours.
[0034] A sodium ion half-cell was prepared and assembled in a glove box filled with argon to characterize the electrochemical performance. The antimony-based composite material prepared in this embodiment was mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce an electrode material. The slurry synthesized in this way was coated on a copper foil with a thickness of 150 μm, and then vacuum dried at 60°C. The dried copper foil was rolled to form a negative electrode. The sodium sheet was used as a reference electrode and a counter electrode, Whatman GF / F glass microfiber was used as a diaphragm, and 1.0M NaClO4 was dissolved in propylene carbonate (PC) as an electrolyte. The battery charge and discharge test was carried out on a blue electric test system. The battery operating range was 0.01-2.5V, the initial discharge specific capacity was 280.3mAh / g, and the discharge specific capacity was 233.6mAh / g after 1000 cycles of discharge at a current density of 1A / g.
[0035] Embodiment 2:
[0036] This embodiment provides an antimony-based composite material which is graphene quantum dots doped with antimony phosphate and has a three-dimensional lamellar structure.
[0037] The preparation method of the antimony-based composite material is as follows:
[0038] The preparation method of graphene quantum dots and 1-aminopropyl-3-methylimidazole phosphate is the same as that of Example 1;
[0039] 0.1 g of graphene quantum dots were dispersed in 10 ml of deionized water to obtain aqueous phase A;
[0040] Add 2.28 g of antimony trichloride to 10 ml of deionized water and mix well to obtain aqueous phase B;
[0041] 2.5 g of Triton X-100, 2.5 g of CTAB, 10 ml of n-butanol, 100 ml of n-hexane and 2.5 g of 1-aminopropyl-3-methylimidazole phosphate were mixed to obtain an oil phase, and the oil phase was evenly divided into two parts, denoted as oil phase A and oil phase B, and water phase A and water phase B were added to oil phase A and oil phase B respectively and stirred to obtain microemulsion A and microemulsion B;
[0042] After microemulsion A and microemulsion B are mixed, they are rapidly stirred at a speed of 500 r / min for 10 minutes to obtain a mixed reaction liquid. The mixed reaction liquid is transferred to a hydrothermal reactor, sealed and heated to 105°C for reaction for 10 hours. After the reaction is completed, the room temperature is restored and centrifuged. The product is collected, repeatedly washed with deionized water and anhydrous ethanol, and then vacuum dried at 60°C for 24 hours.
[0043] A sodium ion half-cell was prepared and assembled in a glove box filled with argon to characterize the electrochemical performance. The antimony-based composite material prepared in this embodiment was mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce an electrode material. The slurry synthesized in this way was coated on a copper foil with a thickness of 150 μm, and then vacuum dried at 60°C. The dried copper foil was rolled to form a negative electrode. The sodium sheet was used as a reference electrode and a counter electrode, Whatman GF / F glass microfiber was used as a diaphragm, and 1.0M NaClO4 was dissolved in propylene carbonate (PC) as an electrolyte. The charge and discharge test of the battery was carried out on a blue electric test system. The battery operating range was 0.01-2.5V, the initial discharge specific capacity was 292.5mAh / g, and the discharge specific capacity was 248.1mAh / g after 1000 cycles of discharge at a current density of 1A / g.
[0044] Embodiment 3:
[0045] This embodiment provides an antimony-based composite material which is graphene quantum dots doped with antimony phosphate and has a three-dimensional lamellar structure.
[0046] The preparation method of the antimony-based composite material is as follows:
[0047] The preparation method of graphene quantum dots and 1-aminopropyl-3-methylimidazole phosphate is the same as that of Example 1;
[0048] 0.1 g of graphene quantum dots were dispersed in 10 ml of deionized water to obtain aqueous phase A;
[0049] Add 2.28 g of antimony trichloride to 10 ml of deionized water and mix well to obtain aqueous phase B;
[0050] 2.5 g of Triton X-100, 2.5 g of CTAB, 10 ml of n-butanol, 100 ml of n-hexane and 2.5 g of 1-aminopropyl-3-methylimidazole phosphate were mixed to obtain an oil phase, and the oil phase was evenly divided into two parts, denoted as oil phase A and oil phase B, and water phase A and water phase B were added to oil phase A and oil phase B respectively and stirred to obtain microemulsion A and microemulsion B;
[0051] After microemulsion A and microemulsion B are mixed, they are rapidly stirred at a speed of 500 r / min for 10 minutes to obtain a mixed reaction liquid. The mixed reaction liquid is transferred to a hydrothermal reactor, sealed and heated to 110°C for reaction for 10 hours. After the reaction is completed, the room temperature is restored and centrifuged. The product is collected, repeatedly washed with deionized water and anhydrous ethanol, and then vacuum dried at 60°C for 24 hours.
[0052] A sodium ion half-cell was prepared and assembled in a glove box filled with argon to characterize the electrochemical performance. The antimony-based composite material prepared in this embodiment was mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce an electrode material. The slurry synthesized in this way was coated on a copper foil with a thickness of 150 μm, and then vacuum dried at 60°C. The dried copper foil was rolled to form a negative electrode. The sodium sheet was used as a reference electrode and a counter electrode, Whatman GF / F glass microfiber was used as a diaphragm, and 1.0M NaClO4 was dissolved in propylene carbonate (PC) as an electrolyte. The battery charge and discharge test was carried out on a blue electric test system. The battery operating range was 0.01-2.5V, the initial discharge specific capacity was 300.4mAh / g, and the discharge specific capacity was 251.6mAh / g after 1000 cycles of discharge at a current density of 1A / g.
[0053] Embodiment 4:
[0054] This embodiment provides an antimony-based composite material which is graphene quantum dots doped with antimony phosphate and has a three-dimensional lamellar structure.
[0055] The preparation method of the antimony-based composite material is as follows:
[0056] The preparation method of graphene quantum dots and 1-aminopropyl-3-methylimidazole phosphate is the same as that of Example 1;
[0057] 0.1 g of graphene quantum dots were dispersed in 10 ml of deionized water to obtain aqueous phase A;
[0058] Add 2.28 g of antimony trichloride to 10 ml of deionized water and mix well to obtain aqueous phase B;
[0059] 2.5 g of Triton X-100, 2.5 g of CTAB, 10 ml of n-butanol, 100 ml of n-hexane and 2.5 g of 1-aminopropyl-3-methylimidazole phosphate were mixed to obtain an oil phase, and the oil phase was evenly divided into two parts, denoted as oil phase A and oil phase B, and water phase A and water phase B were added to oil phase A and oil phase B respectively and stirred to obtain microemulsion A and microemulsion B;
[0060] After microemulsion A and microemulsion B are mixed, they are rapidly stirred at a speed of 500 r / min for 10 minutes to obtain a mixed reaction liquid. The mixed reaction liquid is transferred to a hydrothermal reactor, sealed and heated to 115°C for reaction for 10 hours. After the reaction is completed, the room temperature is restored and centrifuged. The product is collected, repeatedly washed with deionized water and anhydrous ethanol, and then vacuum dried at 60°C for 24 hours.
[0061] A sodium ion half-cell was prepared and assembled in a glove box filled with argon to characterize the electrochemical performance. The antimony-based composite material prepared in this embodiment was mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce an electrode material. The slurry synthesized in this way was coated on a copper foil with a thickness of 150 μm, and then vacuum dried at 60°C. The dried copper foil was rolled to form a negative electrode. The sodium sheet was used as a reference electrode and a counter electrode, Whatman GF / F glass microfiber was used as a diaphragm, and 1.0M NaClO4 was dissolved in propylene carbonate (PC) as an electrolyte. The battery charge and discharge test was carried out on a blue electric test system. The battery operating range was 0.01-2.5V, the initial discharge specific capacity was 284.2mAh / g, and the discharge specific capacity was 244.8mAh / g after 1000 cycles of discharge at a current density of 1A / g.
[0062] Embodiment 5:
[0063] This embodiment provides an antimony-based composite material which is graphene quantum dots doped with antimony phosphate and has a three-dimensional lamellar structure.
[0064] The preparation method of the antimony-based composite material is as follows:
[0065] The preparation method of graphene quantum dots and 1-aminopropyl-3-methylimidazole phosphate is the same as that of Example 1;
[0066] 0.1 g of graphene quantum dots were dispersed in 10 ml of deionized water to obtain aqueous phase A;
[0067] Add 2.28 g of antimony trichloride to 10 ml of deionized water and mix well to obtain aqueous phase B;
[0068] 2.5 g of Triton X-100, 2.5 g of CTAB, 10 ml of n-butanol, 100 ml of n-hexane and 2.5 g of 1-aminopropyl-3-methylimidazole phosphate were mixed to obtain an oil phase, and the oil phase was evenly divided into two parts, denoted as oil phase A and oil phase B, and water phase A and water phase B were added to oil phase A and oil phase B respectively and stirred to obtain microemulsion A and microemulsion B;
[0069] After microemulsion A and microemulsion B are mixed, they are rapidly stirred at a speed of 500 r / min for 10 minutes to obtain a mixed reaction liquid. The mixed reaction liquid is transferred to a hydrothermal reactor, sealed and heated to 120°C for reaction for 10 hours. After the reaction is completed, the room temperature is restored and centrifuged. The product is collected, repeatedly washed with deionized water and anhydrous ethanol, and then vacuum dried at 60°C for 24 hours.
[0070] A sodium ion half-cell was prepared and assembled in a glove box filled with argon to characterize the electrochemical performance. The antimony-based composite material prepared in this embodiment was mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce an electrode material. The slurry synthesized in this way was coated on a copper foil with a thickness of 150 μm, and then vacuum dried at 60°C. The dried copper foil was rolled to form a negative electrode. The sodium sheet was used as a reference electrode and a counter electrode, Whatman GF / F glass microfiber was used as a diaphragm, and 1.0M NaClO4 was dissolved in propylene carbonate (PC) as an electrolyte. The battery charge and discharge test was carried out on a blue electric test system. The battery operating range was 0.01-2.5V, the initial discharge specific capacity was 276.9mAh / g, and the discharge specific capacity was 240.7mAh / g after 1000 cycles of discharge at a current density of 1A / g.
[0071] By comparing Examples 1-5, it can be seen that the different hydrothermal reaction temperatures of the microemulsion have an impact on its electrochemical properties. When the hydrothermal reaction temperature is 110° C., the antimony-based composite material prepared has the best electrochemical properties.
[0072] Comparative Example 1:
[0073] The method is basically the same as Example 1, except that commercially available graphene quantum dots (Suzhou Kaifa New Material Technology Co., Ltd.) are used instead of the homemade graphene quantum dots;
[0074] A sodium ion half-cell was prepared and assembled in a glove box filled with argon to characterize the electrochemical performance. The antimony-based composite material prepared in this comparative example was mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce an electrode material. The slurry synthesized was coated on a copper foil with a thickness of 150 μm, and then vacuum dried at 60°C. The dried copper foil was rolled to prepare a negative electrode. The sodium sheet was used as a reference electrode and a counter electrode, Whatman GF / F glass microfiber was used as a diaphragm, and 1.0M NaClO4 was dissolved in propylene carbonate (PC) as an electrolyte. The battery charge and discharge test was carried out on a blue electric test system. The battery working range was 0.01-2.5V, the initial discharge specific capacity was 254.2mAh / g, and the discharge specific capacity was 192.6mAh / g after 1000 cycles of discharge at a current density of 1A / g.
[0075] By comparing Example 1 with Comparative Example 1, it can be seen that the graphene quantum dots prepared by the present invention can improve the electrochemical performance of the antimony-based composite material to a greater extent than the commercially available graphene quantum dots.
[0076] Comparative Example 2:
[0077] The method is basically the same as Example 1, except that commercially available graphene oxide (Beijing Meiston Technology Development Co., Ltd.) is used instead of the homemade graphene quantum dots;
[0078] A sodium ion half-cell was prepared and assembled in a glove box filled with argon to characterize the electrochemical performance. The antimony-based composite material prepared in this comparative example was mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce an electrode material. The slurry synthesized was coated on a copper foil with a thickness of 150 μm, and then vacuum dried at 60°C. The dried copper foil was rolled to prepare a negative electrode. The sodium sheet was used as a reference electrode and a counter electrode, Whatman GF / F glass microfiber was used as a diaphragm, and 1.0M NaClO4 was dissolved in propylene carbonate (PC) as an electrolyte. The battery charge and discharge test was carried out on a blue electric test system. The battery operating range was 0.01-2.5V, the initial discharge specific capacity was 212.6mAh / g, and the discharge specific capacity was 153.7mAh / g after 1000 cycles of discharge at a current density of 1A / g.
[0079] By comparing Example 1 with Comparative Example 2, it can be seen that the graphene quantum dots prepared by the present invention can improve the electrochemical performance of antimony-based composite materials to a greater extent than commercially available graphene oxide.
[0080] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an antimony-based composite material, characterized in that: Dispersing graphene quantum dots in deionized water to obtain aqueous phase A; Add antimony trichloride into deionized water and mix well to obtain aqueous phase B; A surfactant, n-butanol, an organic solvent and 1-aminopropyl-3-methylimidazole phosphate are mixed to obtain an oil phase, the oil phase is divided into two parts, namely oil phase A and oil phase B, and water phase A and water phase B are added to oil phase A and oil phase B respectively and stirred to obtain microemulsion A and microemulsion B; After mixing microemulsion A and microemulsion B, quickly stir to obtain a mixed reaction liquid, transfer the mixed reaction liquid to a hydrothermal reactor, seal and heat to 100-120°C for 1-10 hours, return to room temperature after the reaction, centrifuge, collect the product, wash and dry; The preparation method of the 1-aminopropyl-3-methylimidazole phosphate is as follows: 1-aminopropyl-3-methylimidazolium bromide is added to deionized water, and the resulting solution is passed through an anion exchange resin to obtain an ionic liquid hydroxide solution. Phosphoric acid is added to the ionic liquid hydroxide solution, and after stirring at room temperature for 24 hours, dichloromethane is added for extraction, and the dichloromethane phase is separated, concentrated under reduced pressure, and then dried in vacuum; The preparation method of the graphene quantum dots is as follows: Add graphene oxide to nitric acid, ultrasonically oscillate to form a dispersion, heat the dispersion to 60-80°C for reaction for 12-48 hours, cool to room temperature, adjust the pH of the solution to 7-8, then dialyze with a dialysis bag for 1-5 days, transfer the dialysate to a hydrothermal reactor, hydrothermally react at 100-120°C for 5-10 hours, cool to room temperature, add concentrated sulfuric acid, continue to hydrothermally react at 120-150°C for 5-10 hours, cool to room temperature, adjust the pH of the solution to 7-8, dialyze the reaction solution with a dialysis bag again for 1-5 days, centrifuge the dialysate, remove large precipitates, and then freeze-dry.
2. The method for preparing the antimony-based composite material according to claim 1, characterized in that: The molecular weight cut-off of the dialysis bag is 1500-3500Da.
3. The method for preparing the antimony-based composite material according to claim 1, characterized in that: The surfactant consists of Triton X-100 and CTAB.
4. The method for preparing the antimony-based composite material according to claim 3, characterized in that: The mass ratio of Triton X-100 to CTAB is 1-4:1-4.
5. The method for preparing the antimony-based composite material according to claim 1, characterized in that: The organic solvent is any one of n-pentane, n-hexane, n-heptane and n-octane, or a combination of two or more thereof.
6. An antimony-based composite material prepared by the method for preparing an antimony-based composite material according to any one of claims 1 to 5, characterized in that: The antimony-based composite material is graphene quantum dots doped with antimony phosphate, and the graphene quantum dots doped with antimony phosphate has a three-dimensional lamellar structure.
7. Use of the antimony-based composite material as claimed in claim 6 in a negative electrode material for a sodium ion battery.
Citation Information
Patent Citations
Negative electrode material based on Sb / Sn phosphate as well as preparation method and application of negative electrode material in sodium-ion battery
CN108899499A
Graphene supported SbVO4 nanoparticle composite material and preparation method thereof
CN109473666A